Optimal Design of Reverse-six-link Mechanism of Type ZL50 Loader - Chen Xinde (Jixie chuandong)
In consideration of the effect of the work stroke of lifting cylinder and bucket cylinder on the working performance of loader,the work strokes of the two cylinders are then selected to be design variables together with the position coordinates of the pivot points of the reverse-six-link mechanism,at the same time,the optimization objective is set to improve the ratio of transferring force of lifting cylinder under the condition of meeting the performance indexes and other constraints. With the help of ADAMS/View software,a parameterized model of reverse-six-link mechanism of type ZL50 loader is built,and optimization design is carried out. The design result shows that the translation performance and the unload distance,as well as the ratio of transferring force of lifting cylinder are greatly improved,those requirements of the optimal design are achieved.